A cross-sectional survey on the effectiveness of public health campaigns for changing knowledge, attitudes, and practices in Kenyan informal settlements during the COVID-19 pandemic. - Steven Scholfield; Geraldine D Kavembe; Rodney R Duncan; Bernhards O Ragama; Jared Mecha; Albert Orwa; Geoffrey Otomu; Erick Wanga; James Astleford; John Gutto; Isaac Kibwage; Julius Ogato; et al. (PLoS ONE)
We performed two cross-sectional surveys across three informal settlements in Kenya (within Kisii county, Nairobi, and Nakuru county) to study the effectiveness of public health interventions during the COVID-19 pandemic. A total of 720 participants were surveyed from 120 randomly selected geographical locations (240 participants/settlement/survey), and a coordinated health promotion campaign was delivered between the two surveys by trained staff. Information relating to knowledge, attitudes, and practices (KAP) were collected by trained field workers using a validated questionnaire. The main outcomes showed improvements in: (i) mask-wearing (% of participants 'Always' using their mask increased from 71 to 74%, and the percentage using their masks 'Sometimes' decreased from 15% to 6%; p<0.001); (ii) practices related to face mask usage (% of subjects covering the mouth and nose increased from 91 to 95%, and those covering only part of their face decreased from around 2.5% to <1%; p<0.001). Significant improvements were also seen in the attitudes and expectations relating to mask wearing, and in the understanding of government directives. Over 50% of subjects in the post-campaign survey reported that social distancing was not possible in their communities and fears associated with COVID-19 testing were resistant to change (unchanged at 10%). Access to COVID-19 testing facilities was limited, leaving a large proportion of people unable to test. As willingness to take a COVID-19 test did not change between surveys (69 vs 70%; p = 0.57), despite increased availability, we recommend that policy level interventions are needed, aimed at mitigating adverse consequences of a positive test. Improvements of KAPs in the more crowded urban environment (Nairobi) were less than at settlements in rural or semi-urban settings (Nakuru and Kisii). We conclude that coordinated public health campaigns are effective in facilitating the change of KAPs amongst people living amidst challenging socio-economic conditions in informal settlements.